Constipation treatment safety at pregnancy - O. Z. Okhlobystina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present literature data on development and treatment of constipation at pregnancy.Original positions. Pregnant women, who suffer of constipation, ingest less amount of products, containing plant fibers and less water. It is supposed, that high progesteron level during pregnancy results in increased production of renin, activation of rennin-angiotensinaldosterone system causes increased absorption of water in the large intestine. In late pregnancy the large intestine is pushed aside and compressed by enlarged uterus that can impair passage of fecal masses and provoke constipation. Polyethylene glycol-containing laxatives, are safe and recommended as treatment of choice in constipation at pregnant and breast-feeding women. Macrogol-4000 is not metabolized and not absorbed, having therefore no undesirable effect on fetus.Conclusion. Treatment of constipation during pregnancy should begin with nonpharmaceutical methods. However, if sure nutrition, keeping of proper lifestyle and moderate physical activity do not result in desirable effect, drugs should be prescribed. Macrogol 4000 is effective and safe at pregnancy even at long-term intake.